PERAN GURU BIMBINGAN DAN KONSELING MENGEMBANGKAN KECERDASAN INTERPERSONAL KELAS XI SMAN 3 - Ahgni, Nur; Asrori, M; Wicaksono, Luhur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe role of guidance and counseling teacher is to help students to be able to understand themselves and be able to develop their potential to the fullest. One potential that must be developed by students is interpersonal intelligence. The purpose of this study was to obtain objective information and describe the role of the guidance and counseling teacher in developing interpersonal intelligence of class XI students of State Senior High School 3 Pontianak. The method used in this research is a descriptive method with a quantitative approach and uses survey research forms. The population that became the source of data in this study were all students of class XI with a population of 329 students with a sample of 49 students who were respondents. Data collection techniques in this study are indirect communication techniques. Data collection tool in this study was a questionnaire. Based on the results of data analysis showed that students' interpersonal intelligence reached 73.39% including the good category. While the role of guidance and counseling teachers in developing interpersonal intelligence of class XI students of State Senior High School 3 Pontianak reached 80.76% included in both categories.Â Keywords: Teacher Role, Guidance and Counseling, Interpersonal Intelligence